Inhibition of Autophagy at Different Stages by ATG5 Knockdown and Chloroquine Supplementation Enhances Consistent Human Disc Cellular Apoptosis and Senescence Induction rather than Extracellular Matrix Catabolism - Ito, Masaaki (Int J Mol Sci, 2021)
The intervertebral disc is the largest avascular organ. Autophagy is an important cell survival mechanism by self-digestion and recycling damaged components under stress, primarily nutrient deprivation. Resident cells would utilize autophagy to cope with the harsh disc environment. Our objective was to elucidate the roles of human disc cellular autophagy. In human disc cells, serum deprivation and pro-inflammatory interleukin-1β (IL-1β) stimulation increased autophagy marker microtubule-associated protein 1 light chain 3 (LC3)-II and decreased autophagy substrate p62/sequestosome 1 (p62/SQSTM1), indicating enhanced autophagy. Then, RNA interference (RNAi) of autophagy-related gene 5 (ATG5), essential for autophagy, showed decreases in ATG5 protein (26.8%–27.4%, p < 0.0001), which suppressed early-stage autophagy with decreased LC3-II and increased p62/SQSTM1. Cell viability was maintained by ATG5 RNAi in serum-supplemented media (95.5%, p = 0.28) but reduced in serum-free media (80.4%, p = 0.0013) with IL-1β (69.9%, p = 0.0008). Moreover, ATG5 RNAi accelerated IL-1β-induced changes in apoptosis and senescence. Meanwhile, ATG5 RNAi unaffected IL-1β-induced catabolic matrix metalloproteinase release, down-regulated anabolic gene expression, and mitogen-activated protein kinase pathway activation. Lysosomotropic chloroquine supplementation presented late-stage autophagy inhibition with apoptosis and senescence induction, while catabolic enzyme production was modest. Disc-tissue analysis detected age-related changes in ATG5, LC3-II, and p62/SQSTM1. In summary, autophagy protects against human disc cellular apoptosis and senescence rather than extracellular matrix catabolism.